Cause for Alarm : the Volunteer Fire Department in the Nineteenth-Century City. - Greenberg, Amy S. (Princeton legacy library., 2014)
Though central to the social, political, and cultural life of the nineteenth-century city, the urban volunteer fire department has nevertheless been largely ignored by historians. Redressing this neglect, Amy Greenberg reveals the meaning of this central institution by comparing the fire departments of Baltimore, St. Louis, and San Francisco from the late eighteenth to the mid-nineteenth century. Volunteer fire companies protected highly flammable cities from fire and provided many men with friendship, brotherhood, and a way to prove their civic virtue. While other scholars have claimed tha.